Radiogenic isotope geochemistry : a guide for industry professionals - Schaefer, Bruce F., 1972- (Cambridge University Press, 2016)
"Isotopes provide important information on many geological processes, with key relevance to the mining and petroleum industries, yet the techniques to obtain, process and interpret the data can be complex to master. This accessible book provides broad coverage of radiogenic isotopes in geochronology and geochemistry, explaining the basic principles and state-of-the-art techniques used to study them, with an emphasis on industry applications. The major isotopic systems are fully summarised with relation to real-world applications, enabling readers to decide which technique is most relevant for the problem they want to solve, and then to rigorously evaluate existing data, or recalculate and reassess datasets to avoid duplication of effort. A comprehensive glossary clarifies the numerous acronyms used in the field. Written at a level appropriate for advanced undergraduate students, the book also includes detail which allows more experienced practitioners to maximise the potential value of isotopic datasets. Provides a summary of isotopic systems, allowing quick identification and assessment of whether a system is the correct one for use on a specific problem, Gives insight into analytical techniques, with a short summary of the instrumentation and how data is obtained, enabling the reader to understand the limitations of the data they are using, Key concepts and applications are reinforced throughout the book, enabling the reader to 'dip in' and discover answers rather than requiring a linear reading"--The publsiher